Повести Белкина - Пушкин Александр Сергеевич (Отрочество, 1991)
Экземпляры: ф.18 (20160127) / Инвентарный номер: 479 / Цена: / Сис.шифр: 84(2Рос=Рус)1-4 / Авт.знак: П 91 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)1-44